ANALYSIS OF STUDENT’S MISCONCEPTIONS ON DYNAMIC FLUID CONCEPTS USING THE FOUR-TIER DIAGNOSTIC TEST METHOD - Vivi Mardian; Fanny Rahmatina Rahim (Pendidikan IPA, FMIPA, UNP, 2021)
The learning process is carried out fully in the network during the Covid-19 outbreak so that the use of learning media becomes one of the determinants of students' success in learning. Lack of application of learning media while online causes misconceptions in students. Based on previous research, 28% of students experienced misconceptions in dynamic fluid material with sub-matter continuity. The study was conducted to identify student misconceptions on dynamic fluid material using the four-tier diagnostic test method. The four-tier diagnostic test instrument used in this study was 5 questions tested to 17 grade XI students at one of the high schools in Tanah Datar. The stages of research were carried out as follows: 1) making diagnostic test instruments form four-tier diagnostic tests, 2) data collection, 4) data processing and analysis, 5) conclusion making. Based on data analysis and results of identification of student conception category on dynamic fluid material, 31% of students were in the concept-savvy category, 9% of students were in partial concepts category, 25% of students were in the conceptless category, and 39% of students were in the concept of misconceptions.